2002
DOI: 10.1128/iai.70.12.6726-2733.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal DNA Deletions Explain Phenotypic Characteristics of Two Antigenic Variants, Phase II and RSA 514 (Crazy), of theCoxiella burnetiiNine Mile Strain

Abstract: After repeated passages through embyronated eggs, the Nine Mile strain of Coxiella burnetii exhibits antigenic variation, a loss of virulence characteristics, and transition to a truncated lipopolysaccharide (LPS) structure. In two independently derived strains, Nine Mile phase II and RSA 514, these phenotypic changes were accompanied by a large chromosomal deletion (M. H. Vodkin and J. C. Williams, J. Gen. Microbiol. 132:2587-2594, 1986). In the work reported here, additional screening of a cosmid bank prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 54 publications
9
130
0
Order By: Relevance
“…Recent microarray analysis of the genomes of NMI and NMII has confirmed that the only difference between these strains, at the gene-deletion level, is a Ϸ26-kb deletion in NMII that eliminates a number of genes involved in LPS biosynthesis (ref. 3 and P. Beare and R.A.H., unpublished work). It would therefore seem logical to hypothesize that truncated NMII LPS directly stimulates DC, whereas full-length NMI LPS does not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent microarray analysis of the genomes of NMI and NMII has confirmed that the only difference between these strains, at the gene-deletion level, is a Ϸ26-kb deletion in NMII that eliminates a number of genes involved in LPS biosynthesis (ref. 3 and P. Beare and R.A.H., unpublished work). It would therefore seem logical to hypothesize that truncated NMII LPS directly stimulates DC, whereas full-length NMI LPS does not.…”
Section: Discussionmentioning
confidence: 99%
“…C. burnetii strains of decreased or no virulence in animal models have been generated through serial in vitro passage. These isogenic strains have undergone a ''phase variation'' event in which a chromosomal mutation affecting LPS biosynthesis has occurred (3). Avirulent or ''phase II'' bacteria, typified by the Nine Mile phase II (NMII) strain, produce an LPS that lacks the unique branched terminal sugar-containing O-polysaccharide chain that is characteristic of the LPS of virulent or ''phase I'' organisms, such as the Nine Mile phase I (NMI) strain (4).…”
Section: T He Obligate Intracellular Gram-negative Bacterial Pathogenmentioning
confidence: 99%
“…Yet the LPS of C. burnetii has an endotoxic activity 100 to 1 000 times lower than that of the LPS of Enteriobacteriaceae [4], but it induces the production of inflammatory cytokines in murine and human macrophages [35,171]. Avirulent phase II bacteria are produced by spontaneous mutations or large genetic rearrangements that result in the synthesis of truncated forms of LPS, which lack the branched-chain sugars virenose and dihydrohydroxystreptose present in phase I LPS [64,65,164]. This phase variation is observed when Coxiella organisms are propagated in non-immunocompetent cell cultures or hen eggs and is irreversible [122].…”
Section: Bacteriologymentioning
confidence: 99%
“…Phase I bacteria are virulent, in contrast to phase II bacteria which are avirulent in immunocompetent animal models of disease (Moos & Hackstadt, 1987;Andoh et al, 2007;Marmion, 2007). The difference in virulence of these strains has been defined as a consequence of differential O-antigen expression (Hoover et al, 2002). One potential reason for our poor understanding of C. burnetii pathobiology is a historical lack of molecular tools for genetic manipulation of the organism.…”
Section: Introductionmentioning
confidence: 99%